2022
DOI: 10.3390/v14112344
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy among Pregnant Women Attending Antenatal Clinics in Pakistan: A Multicentric, Prospective, Survey-Based Study

Abstract: This study aimed to assess the vaccination status and factors contributing to vaccine hesitancy among pregnant women in the largest province of Pakistan. A multicentric, prospective, survey-based study using an interviewer-administered tool was conducted among pregnant women attending antenatal clinics between 1st December 2021 through 30th January 2022 across seven hospitals in Pakistan. The healthcare professionals providing care at the participating hospitals administered the survey. Four hundred and five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Consequently, the coronavirus outbreak has highlighted the necessity for addressing the gender disparity in vaccine aversion, which has mostly been disregarded, except for pregnant cases. Conforming to an investigation on sexual differences in vaccine hesitancy, men were reported more inclined to undergo coronavirus vaccines ( 41 , 42 ). A research investigation conducted on six hundred and seventy-two study participants exhibited a ratio of 67% to the corona vaccination acceptability overall whereas elderly, males, Asians, and graduates were more inclined toward getting vaccinated when compared to their peers ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the coronavirus outbreak has highlighted the necessity for addressing the gender disparity in vaccine aversion, which has mostly been disregarded, except for pregnant cases. Conforming to an investigation on sexual differences in vaccine hesitancy, men were reported more inclined to undergo coronavirus vaccines ( 41 , 42 ). A research investigation conducted on six hundred and seventy-two study participants exhibited a ratio of 67% to the corona vaccination acceptability overall whereas elderly, males, Asians, and graduates were more inclined toward getting vaccinated when compared to their peers ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also revealed more than 37% of the study population was hesitant towards COVID-19 vaccination, with only a limited percentage of unvaccinated patients showing a willingness to receive the COVID-19 vaccine. This is a concern despite levels of COVID-19 vaccine hesitancy being quite similar across many LMICs including Pakistan [ 79 , 80 , 91 ]. As far as the factors associated with hesitancy towards the COVID-19 vaccines are concerned, our study revealed that three-quarters of the hesitant population stated that COVID-19 is not a real problem, followed by COVID-19 vaccines being considered a conspiracy.…”
Section: Discussionmentioning
confidence: 99%
“…The study questionnaire ( Supplementary Material S1 ) was developed from previous surveys conducted by the co-authors on a similar topic and after receiving permission from the corresponding authors to use the questionnaire as a basis for this study [ 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. The content validity of the questionnaire was assessed by a 7-member team comprising medical doctors and pharmacists.…”
Section: Methodsmentioning
confidence: 99%
“…Until now, several studies investigated the determinants of COVID-19 vaccine uptake among pregnant women [ 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. So far, research has focused on the impact of the socio-demographic characteristics on the decision of pregnant women to be vaccinated against COVID-19, e.g., age, ethnicity, race, education, and income.…”
Section: Introductionmentioning
confidence: 99%